Economic development after tin mining: an analysis of strategic policy in economic sector development of Bangka Belitung through the dependency theory - M. Adha Al Kodri; Aimie Sulaiman (Proceedings of AICS - Social Sciences, 2017)
This research describes about the strategic policy of Governor of Bangka Belitung Island Province, Erzaldi Rosman in developing economic sector after tin minning with dependencies theoritical analysis. The research also observe and the interpretation of the about how efforts Erzaldi Rosman use its strategic policy this as a purpose to rebuild foundation economic development Bangka Belitung Island without tin, how policy this strategic can be enjoyed directly and equitable for all people, and how policy this strategic can in line with the human resources development and environmental management. This research itself is conducted by using the method the qualitative study is descriptive with discuss strategic policy done by Ezaldi Rosman in an effort to release dependence economic Bangka Belitung of tin. This research result indicates that there are five strategic policy issued by local government, among other policies on the agricultural, tourism, infrastructure, empowerment small and medium enterprises, and the increase in human resources. Fifth strategic policy is in line with the concept of the theory dependencies said that model the development is maximize factors internal.